Endothelial Cell Indoleamine 2, 3-Dioxygenase 1 Alters Cardiac Function After Myocardial Infarction Through Kynurenine. Issue 6 (9th February 2021) - Melhem, Nada Joe; Chajadine, Mouna; Gomez, Ingrid; Howangyin, Kiave-Yune; Bouvet, Marion; Knosp, Camille; Sun, Yanyi; Rouanet, Marie; Laurans, Ludivine; Cazorla, Olivier; Lemitre, Mathilde; Vilar, José; et al.
Abstract : Background: Ischemic cardiovascular diseases, particularly acute myocardial infarction (MI), is one of the leading causes of mortality worldwide. Indoleamine 2, 3-dioxygenase 1 (IDO) catalyzes 1 rate-limiting step of L-tryptophan metabolism, and emerges as an important regulator of many pathological conditions. We hypothesized that IDO could play a key role to locally regulate cardiac homeostasis after MI. Methods: Cardiac repair was analyzed in mice harboring specific endothelial or smooth muscle cells or cardiomyocyte or myeloid cell deficiency of IDO and challenged with acute myocardial infarction. Results: We show that kynurenine generation through IDO is markedly induced after MI in mice. Total genetic deletion or pharmacological inhibition of IDO limits cardiac injury and cardiac dysfunction after MI. Distinct loss of function of IDO in smooth muscle cells, inflammatory cells, or cardiomyocytes does not affect cardiac function and remodeling in infarcted mice. In sharp contrast, mice harboring endothelial cell–specific deletion of IDO show an improvement of cardiac function as well as cardiomyocyte contractility and reduction in adverse ventricular remodeling. In vivo kynurenine supplementation in IDO-deficient mice abrogates the protective effects of IDO deletion. Kynurenine precipitates cardiomyocyte apoptosis through reactive oxygen species production in an aryl hydrocarbon receptor–dependent mechanism. Conclusions: These data suggest that IDO could constitute a new therapeutic target during acute MI. Abstract : Supplemental Digital Content is available in the text.